Hybrid Respiratory Epithelial Adenomatoid Hamartoma and Seromucinous Hamartoma Clinically Mimicking Bilateral Nasal Polyposis: A Case Report - Raquel Muñoz-Andrés; Carlos Carazo-Casas; Mayte Herrera; Alfonso Santamaría-Gadea; Mónica Garcia-Cosio Piqueras; Kadir Jesús Quintero-Gil (Journal of Otorhinolaryngology, Hearing and Balance Medicine, 2026)
Background: Respiratory epithelial adenomatoid hamartoma (REAH) and seromucinous hamartoma (SH) are uncommon benign epithelial lesions of the sinonasal tract. Their clinical and endoscopic appearance may overlap with inflammatory nasal polyps, and a definitive diagnosis usually requires histopathologic examination. Case presentation: A 37-year-old man presented with several years of nasal obstruction, hyposmia, and facial pressure over the paranasal sinus regions. He had no history of asthma or previous sinonasal surgery. Nasal endoscopy revealed bilateral polypoid lesions involving the middle meatus. Computed tomography showed extensive chronic sinonasal inflammatory disease, including complete opacification of the right maxillary sinus, bilateral frontal sinus involvement, and bilateral ethmoidal opacification. The patient underwent endoscopic sinonasal surgery with bilateral uncinectomy, bilateral antrostomy, and anterior and posterior ethmoidectomy. Polypoid tissue was excised and submitted for histopathologic examination. The final diagnosis was a hybrid epithelial hamartomatous lesion with features of both REAH and SH. At the 4- and 8-week postoperative visit, the patient reported clear symptomatic improvement, mainly in nasal obstruction, smell and nasal breathing. Conclusions: Hybrid REAH and SH may clinically resemble bilateral inflammatory nasal polyposis, especially in patients with chronic rhinosinusitis. This case highlights the importance of routine histopathologic examination of sinonasal polypoid lesions after endoscopic surgery.